2003
DOI: 10.1207/s15374424jccp3204_6
|View full text |Cite
|
Sign up to set email alerts
|

Positive Events as a Stress Buffer for Children and Adolescents in Families in Transition

Abstract: This study examined whether positive events mitigated the relation between negative events and maladjustment in samples of children and adolescents experiencing family transitions. The study examined this relation in two samples, used multiple reporters of maladjustment, and employed "tailor-made" checklists to measure events. The first sample included 86 stepfamilies with adolescents 10 to 17 years of age. The second sample included 171 divorced families with children 8 to 15 years of age. Evidence that posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…This disparity is consistent with the small events and life events literature (Doyle et al 2003;Kanner et al 1991;Reich and Zautra 1988), as well as with an earlier study of parents with acquired physical disabilities and their adolescent children (Mazur 2006). This result challenges clinical psychological and medically oriented research that describes parents with physical disabilities and their families as experiencing intolerable stress (Armistead et al 1995;Iwasaki and Macatavish 2005;Lundwall 2002).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…This disparity is consistent with the small events and life events literature (Doyle et al 2003;Kanner et al 1991;Reich and Zautra 1988), as well as with an earlier study of parents with acquired physical disabilities and their adolescent children (Mazur 2006). This result challenges clinical psychological and medically oriented research that describes parents with physical disabilities and their families as experiencing intolerable stress (Armistead et al 1995;Iwasaki and Macatavish 2005;Lundwall 2002).…”
Section: Discussionsupporting
confidence: 74%
“…Similar to results from studies with adults and adolescents without disabilities (Doyle et al 2003;Kanner et al 1991), Mazur (2006) found that parents with acquired physical disabilities and their adolescent children reported more positive than negative events. Events appraised as positive may increase parents' (Reich and Zautra 1988) and adolescents' adjustment (Doyle et al 2002(Doyle et al , 2003Sandler et al 1991).…”
supporting
confidence: 68%
See 2 more Smart Citations
“…To date, stress generation research has focused exclusively on negative affect and negative life events, despite research demonstrating the stress-buffering effects of positive life events (e.g., Cohen et al 1984;Doyle et al 2003).…”
Section: Discussionmentioning
confidence: 99%